Effect of Copper-Based Fungicide on Chemical Composition of Cocoa Seeds - Lawal, Amudalat Ranti; Olayinka, Bolaji Umar; Olahan, Ganiyu S.; Omorinoye, Omolayo A.; Abdulsalam, Halimat A.; Abdulra'uf, Lukman Bola (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2025)
Production of cocoa seeds, one of Nigeria’s major non-oil foreign exchange earners as well as a major raw material for the beverage industry, is greatly hindered by diseases caused by various species of the genus Phytophthora. To avert this, copper-based fungicides are sprayed on the leaves of cocoa trees to control or prevent the survival of this organism by the farmers without paying attention to the effects of this chemical on the proximate composition of cocoa seeds. This study therefore investigated the effects of a copper-based fungicide (Ridomil Gold Copper) on the quality of the cocoa seeds by spraying cocoa trees, including the pods, with 50.00 g/L of copper-based fungicide. The results obtained showed that cocoa seeds from the control trees showed significantly higher contents of fiber (4.51%), protein (15.1%), and fat (36.1%) when compared to the respective values of 3.45, 3.95, and 7.59% obtained for the cocoa seeds harvested from the fungicide-treated cocoa trees. All other proximate compositions did not show any statistical difference, except for carbohydrate and calorific values, which were significantly higher in cocoa seeds from fungicide-treated cocoa trees. Seeds from fungicide-treated trees showed significantly higher potassium, phosphorus, and magnesium contents but lower zinc and copper contents. However, phytochemicals such as phenols, alkaloids, flavonoids, and tannins were significantly lower in content in the seeds of fungicide-treated cocoa trees. The contents of glycosides and antioxidants in the cocoa seeds were statistically similar for both the control and treatment, except for ascorbic acid, which showed a significantly lower value (4.8 mg/100 ml) in cocoa seeds from fungicide-treated cocoa trees, compared with the value recorded for the control in this study (13.33%). The foregoing results showed that the use of copper-based fungicides for the control of black pod disease in cocoa adversely affected the quality of cocoa seeds from the treated trees.